Which evolutionary status does the Blue Large-Amplitude Pulsators stay at?. Issue 3 (21st May 2018) - Wu, Tao; Li,
ABSTRACT: Asteroseismology is a very useful tool for exploring the stellar interiors and evolutionary status and for determining stellar fundamental parameters, such as stellar mass, radius, surface gravity, and the stellar mean density. In this work, we use it to preliminarily analyse the 14 new type pulsating stars: Blue Large-Amplitude Pulsators (BLAPs) which is observed by O ptical G ravitational L ensing E xperiment project, to roughly analyse their evolutionary status. We adopt the theory of single star evolution and artificially set the mass-loss rate of M=-2× 10^-4 M_ yr ^ -1 and mass-loss beginning at the radius of R = 40 R_ on red giant branch to generate a series of theoretical models. Based on these theoretical models and the corresponding observations, we find that those BLAP stars are more likely to be the core helium burning stars. Most of them are in the middle and late phase of the helium burning.